Digital Estate Planning for Crypto Assets: A Synergetic Analysis of Indonesian Fatwas and Farā’iḍ Principles - Deva Fahreza Haryadi; Musyaffa Amin Ash Shabah (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The significant growth of cryptocurrency adoption in Indonesia, with over 18 million investors by 2025, creates new urgency in contemporary Islamic legal discourse, particularly regarding digital asset inheritance. This article explores the position of cryptocurrency as an inheritance object through evaluation of the requirements of mal in Islamic fiqh. Normative legal research methods with descriptive-analytical approaches analyze primary sources including the Qur'an, Hadith, and MUI Fatwas, along with classical-contemporary fiqh literature. Findings reveal that cryptocurrency fulfills five fundamental requirements as mal: measurable economic value through global market capitalization, legitimate ownership based on private key cryptography, storage capability through digital wallets, halal benefits as a medium of exchange, and public recognition reflected in Bappebti regulations. Cryptocurrency can be categorized as mal ma'nawi with hybrid characteristics combining elements of 'urudh tijariyyah, mal mitsli, mal mutaqawwim, and mal manqul. Although MUI Fatwa Number 116/DSN-MUI/IX/2017 does not explicitly discuss cryptocurrency as an inheritance object, its fundamental principles provide a legitimacy foundation as long as it does not contain riba, excessive gharar, maysir, or illegal purposes. Practical implications reveal significant challenges related to access dependency on private keys. This article recommends developing comprehensive specific fatwas, digital asset inheritance regulations, and increasing Muslim community literacy on cryptocurrency inheritance management.